Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The degree of availability of professional digital skills in the performance of faculty members at The University of Hail From their point of viewCo-Prof. Hatouf Farah Samara, Asst-Prof. Ahlam Ibrahim M. Alhaj Hussein , Asst-Prof. Ghada Alameen Ahmed Suliman , Asst-Prof. Ahlam Elimam Abdalla Yousif2. Teaching mathematics remotely for the elementary level: Challenges and recommendations for development from the teachers viewpointMr. Thamer Nawaf Alrashdi3. An analytical study of contemporary educational issues contained in the websites of educational research and studies centersMr. Mohammed Maudud, Mr. Souleyman Diallo , Dr. Abdulrahman Mohammed N. Alharthi4. Attitudes of Female Master's students in Instructional Technology Program at Najran University towards the Use of Augmented Reality TechnologyMrs. Shroug Mesali Saleh Alyami5. The level of satisfaction of psychological needs based on the realistic model and its relationship to psychological happiness among An-Najah National University studentsMrs. Mays Majed Kahla, Dr. Filasteen Ismail Nazzal6. The reality of primary school teachers' use of educational games in teaching mathematicsMrs. Afrah Essa Al-Najei7. Reflections of Teachers' Participation in the eTwinning platform on Their Professional  and Personal Development in JordanDr. Njoud Yousuf Alananbeh
Keywords: Journal of Educational and Psychological Sciences